Menelaah Hubungan Timbal Balik antara Konflik Internal dengan Masalah Kemiskinan - Chandrawati, Nurani (UI Scholars Hub, 2005)
This article tries to explain the relation between internal armed violence conflict and chronic poverty problems especially in developing countries. There is a close relationship between those two phenomenons. It means that chronic poverty problems could be the main source of the emergence of internal conflict and the other hand internal armed conflict could improve the condition of chronic poverty. Because of that in the process of post-conflict peace-building, reducing chronic poverty through economic development must be an important aim that also could prevent the violence internal conflict in the future and supporting the transformation from conflict situation toward stable peace.